PENERAPAN MODEL FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Riri Ayu; Muhaemin Muhaemin; Makmur Makmur (Fakultas Tarbiyah dan Ilmu Keguruan, 2026)
This study aims to enhance the learning outcomes of seventh-grade students at SMPN 2 Tanalili by implementing the Flipped Classroom learning model in Islamic Religious Education. This classroom action research involved 32 seventh-grade students as participants. Data was collected through observation, documentation, and tests, then analyzed using test sheets and observation sheets. The results of the study indicate that implementing the Flipped Classroom model can improve learning, student engagement, and learning outcomes. The implementation of learning increased from 57% (sufficient category) in cycle I to 94% (very good category) in cycle II. Student activity also increased from 57% (adequate category) to 75% (good category). Student learning outcomes improved from an average score of 44 with a completion rate of 39.6% to an average score of 71 with a completion rate of 80%. Thus, the Flipped Classroom model can enhance student learning outcomes in Islamic Education instruction.